Classifiers and Plurality: evidence from a deictic classifier language - Filomena Sandalo; Dimitris Michelioudakis (Baltic International Yearbook of Cognition, Logic and Communication, 2016)
This paper investigates the semantic contribution of plural morphology and its interaction with classifiers in Kadiwéu. We show that Kadiwéu, a Waikurúan language spoken in South America, is a classifier language similar to Chinese but classifiers are an obligatory ingredient of all determiner-like elements, such as quantifiers, numerals, and wh-words for arguments. What all elements with classifiers have in common is that they contribute an atomized/individualized interpretation of the NP. Furthermore, this paper revisits the relationship between classifiers and number marking and challenges the common assumption that classifiers and plurals are mutually exclusive.
Keywords: plural morphology; classifier language; number marking; kadiweu